Neuromorphic Sensor Network Platform: A Bioinspired Tool to Grow Applications in Wireless Sensor Networks - Mark Richard Wilby; Ana Belén Rodríguez González; Juan José Vinagre Díaz; Jesús Requena Carrión (International Journal of Distributed Sensor Networks)
Wireless Sensor Networks (WSNs) must face the challenge of producing a vast plethora of applications from the least possible number of distributed sensors. In this paper we describe the Neuromorphic Sensor Network (NSN) platform, which implements a bioinspired approach to the development of growing applications in WSNs. NSNs follow an analogy with the neurophysiology of vertebrates, compressing the information coming from sets of sensors in wireless nodes and processing it by means of a set of processing units (PUs) that perform individual general purpose functions. Applications are then constructed through specific connections of these PUs, generating application pathways that allow the reuse of the same distributed NSN to give response to any desired output, thus achieving an application scalability . We illustrate the detailed process of growing applications using the NSN platform through an object tracking tool that mimics the behavior of the vertebrates visual system to detect and track objects. Finally, we describe a real implementation of the NSN platform in a road traffic monitoring and information system currently in operation in the cities of Madrid and Seville (Spain).